1981
DOI: 10.1021/j150609a025
|View full text |Cite
|
Sign up to set email alerts
|

ENDOR study of oxovanadium(IV) tetraphenylporphyrin randomly oriented in rigid solution

Abstract: An ENDOR study has been made of oxovanadium(IV) tetraphenylporphyrin randomly oriented in rigid solution.The ENDOR spectra give information on the 14N hyperfine and quadrupole tensor components as well as the hyperfine tensor components of the pyrrole protons. A comparison of the 14N data obtained here with those previously reported for silver and copper tetraphenylporphyrin clearly establishes the difference in orbital ground state of the d1 2and d9 systems. Using chloroform-toluene as a solvent matrix, we co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 3 publications
4
27
0
Order By: Relevance
“…In addition, we observed no EPR spectrum when only BSA was encapsulated (BSA-SiO 2 sample), showing that the intense line in the middle of the spectrum is not due to organic radicals or defects of the SiO 2 matrix but represents the orientation-independent m I ) -1/2 vanadium hf line. The shape of the spectrum, characterized by narrow hf lines at room temperature, is identical to that of VOTPP in frozen solution at low temperature, 54 which shows that VOTTP is immobilized in silica cages, avoiding tumbling motion. The magnetic parameters deduced from simulation of the spectrum ( Figure 2 and Table 1) are very close to those found for VOTPP in frozen solution, which confirms that the four-fold symmetry of the complex is conserved in SiO 2 and that despite its immobilization, the vanadyl-porphyrin complex is not perturbed by the mineral matrix.…”
Section: Structure Of Vanadyl-porphyrin Trapped In Silica Continuousmentioning
confidence: 69%
See 1 more Smart Citation
“…In addition, we observed no EPR spectrum when only BSA was encapsulated (BSA-SiO 2 sample), showing that the intense line in the middle of the spectrum is not due to organic radicals or defects of the SiO 2 matrix but represents the orientation-independent m I ) -1/2 vanadium hf line. The shape of the spectrum, characterized by narrow hf lines at room temperature, is identical to that of VOTPP in frozen solution at low temperature, 54 which shows that VOTTP is immobilized in silica cages, avoiding tumbling motion. The magnetic parameters deduced from simulation of the spectrum ( Figure 2 and Table 1) are very close to those found for VOTPP in frozen solution, which confirms that the four-fold symmetry of the complex is conserved in SiO 2 and that despite its immobilization, the vanadyl-porphyrin complex is not perturbed by the mineral matrix.…”
Section: Structure Of Vanadyl-porphyrin Trapped In Silica Continuousmentioning
confidence: 69%
“…In their ENDOR study of VOTPP in frozen solution, Mulks and Van Willigen observed this doublet in pyridine but not in CHCl 3 . 54 This variability indicates that it is most probably due to an axial water molecule impurity present in the solvent, forming a H 2 O · · · VdO bond parallel to the C 4 axis. Our DFT calculations predict proton hf parameters a iso ) +0.1 MHz and T ) +4.5 MHz for this axial water molecule (Table 2).…”
Section: Structure Of Vanadyl-porphyrin Trapped In Silica Continuousmentioning
confidence: 99%
“…Oxovanadium͑IV͒ tetraphenylporphyrin, VO͑TPP͒, complexes are extensively used in EPR studies to probe biomolecular structures, [19][20][21] where the VO 2ϩ ion substitutes for a variety of divalent metal ions in metal-activated enzymes and metalloproteins, 18,22 or as models for acid demetallization in crude oils. 23 Here, we illustrate the versatility of RAW-EPR on VO͑TPP͒ in frozen CHCl 3 -toluene solution.…”
Section: Raw-epr Of Oxovanadium"iv… Tetraphenylporphyrinmentioning
confidence: 99%
“…One of the most active was that of Selbin, the author of two of the few reviews published concerning V IV O-compounds [2,3]. Some other relevant groups were those of Gillard [4,5], Kustin [6][7][8], Chasteen [9][10][11], Rieger [12][13][14], Tapscott [15,16], McCormic [17], Syamal [18][19][20][21][22], Wasson and Stoklosa [23,24], Saito [25][26][27], VanWilligen [28,29], Nicholls [30][31][32], Fraústo da Silva [5,33], Theriot [21,[34][35][36], Riechel [37], Floriani [38] and some others.…”
Section: Introductionmentioning
confidence: 99%